Eigengame: a primer to introduce wave functions and probabilities - Sabater, Francesc; Calero, Carles; Juliá-Díaz, Bruno (Frontiers in Quantum Science and Technology, 2023)
We report on a quantum mechanics popularisation software, Eigengame, developed to get general audiences to play with key concepts in quantum mechanics, i.e. the wave function, the quantization of energy, the probability density and, to some extent, the measurement problem. The software is developed in python and is available online at github.